Improving Basketball Passing Techniques through a Problem-Based Learning Approach - Hasibuan, Ahmad Riady; Syafrayani, Putri Rizki (Al'Adzkiya Journal, 2024)
This study aims to enhance passing technique skills in basketball using a Problem-Based Learning (PBL) model at SMA Negeri 11 Medan, incorporating audio-visual media. Employing a quantitative method, the study involved a population and sample of 36 students from Class XI IPA 1 at SMA Negeri 11 Medan. The variables in this research include the Problem-Based Learning (PBL) model, audio-visual learning media, and learning outcomes. The results of the independent t-sample test showed a significance value of 0.000, which is less than 0.05, indicating a significant difference between the learning outcomes of students using the PBL model and those using conventional learning methods. The average score of students using the PBL model was 83.89, while the average score of students using conventional learning methods was not reported in this paragraph.